Kurikulum dan Tuntutan Kompetensi Abad 21 - Umam, Khairul (Nusantara: Jurnal Pendidikan Indonesia, 2021)
The purpose of this study is to determine the role of the curriculum in facing the demands of 21st century competence. The topic of discussion is the identification of 21st century competencies of relevant learning styles in the 21st century, as well as innovations that can be applied to support success in learning activities. The method used in this research is library research, namely reviewing books and related sources to support research data. The results of this study show the importance of knowing the skills required in the 21st century, besides that innovation in education is needed to adapt to the needs of the times.